A comparative study of structural, electrical and dielectric properties of Ni-Zn and Co-Zn nanoferrites. (2022) - Chahar, Deepika; Thakur, Preeti; Thakur, Atul
Abstract: Ni-Zn ferrite and Co-Zn ferrite having composition Ni0.5 Zn0.5 Fe2 O4 and Co0.5 Zn0.5 Fe2 O4 were synthesized using citrate precursor method. Single phase cubic spinel structure with space group Fd3m was confirmed by X-ray diffraction (XRD) studies of the prepared samples. The crystallite size was found to be 42 nm and 28 nm for Ni-Zn and Co-Zn nanoferrites respectively. The FTIR spectra showed the metal stretching vibrations at tetrahedral sites and octahedral sites for both the ferrites. The dielectric and electrical study was done to calculate various parameters like dielectric loss tangent and dc resistivity. The prepared ferrites are found to have good insulating properties due to high value of dc resistivity with values 5.39 × 10 10  Ω-cm for Ni-Zn ferrite and 3.4 × 10 10  Ω-cm for Co-Zn ferrite. Also, due to low value of loss tangent at high frequency i.e. 0.05 at 1 MHz for Ni-Zn nanoferrite, these ferrites may be used in the high frequency applications.